PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR PERSONAL SELF-DEVELOPMENT OF STUDENTS IN THE PROCESS HIGHER EDUCATION - N.I. Zelenkova (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the peculiarities of psychological and pedagogical support of students' personal own development in the process of interactive training.